Margaret Thatcher et la BBC : régulation ou manipulation ? - Daniel Ruff (Revue LISA)
This article argues that the relationship between Margaret Thatcher and her governments of the 1980s on the one hand, and the BBC on the other, differed from those of an ‘arm’s length’ regulator which had existed since the creation of the BBC through successive Conservative and Labour governments until 1979, in which ministers would not intervene in BBC policy or programming. Ministers and party members instituted a concerted attempt to intimidate the BBC, most especially its news and current affairs programmes, whenever the latter did not report national politics and international events to the government’s liking. Proposed neo-liberal reforms to the system of funding the Corporation and negotiations for regular increases in the value of the licence fee were similarly opportunities to exert pressure on the BBC and to call into question its public service remit. Finally, royal prerogative and royal patronage were used to manipulate the political colour of the Board of Governors and thus, indirectly, the management of the BBC.